Behavior Change Techniques and the Effects Associated With Digital Behavior Change Interventions in Sedentary Behavior in the Clinical Population: A Systematic Review. - Martín-Martín, Jaime; Roldán-Jiménez, Cristina; De Torres García, Irene; Muro Culebras, Antonio Luis; Escriche-Escuder, Adrián; González-Sánchez, Manuel; Ruiz-Muñoz, María; Mayoral Cleries, Fermín; Biró, Attila; Tang, Wen; Nikolova, Borjanka; Salvatore, Alfredo; et al. (Frontiers, 2021)
This systematic review aimed to evaluate the most frequently used behavior change techniques (BCTs) in digital health interventions targeting sedentary behavior (SB) and to review their effects. Eighteen randomized clinical trials (RCTs) were included, involving both healthy adults and individuals with a disease. The most commonly employed digital behavior change interventions (DBCI) for SB included goal setting, problem solving, outcome/goal review, feedback on behavior and outcomes, behavioral self-monitoring, social support, information about health consequences, and behavioral practice/rehearsal. The effects of DBCIs showed improvements in physical activity (PA) and self-reported physiological and anthropometric outcomes. However, the study also highlighted that the effectiveness of DBCIs is influenced by various factors such as intervention type, patient preferences and values, and the number of BCTs employed. Further research is needed to determine the most effective DBCIs and BCTs for reducing SB in the clinical population.
Keywords: Conducta; Change; Digital interventions; Technique; Sedentary behavior; Behavior